Edukasi Pentingnya Pendidikan Tinggi Dalam Merespon Kawasan Industri Terpadu Batang - Setiawan, Hendy; Erison, Yendra; Choirunnisa, Choirunnisa (Universitas Negeri Gorontalo, 2024)
Human resources are a problem that Batang Regency is still experiencing. Many policies have been and are being launched by the regional government and do not have enough impact. Therefore, with the situation experienced, the low level of human resources has become a complicated problem for the Batang Integrated Industrial Zone (KITB). The purpose of this article is to educate students at SMK Ma'arif 01 Limpung to be motivated to continue their studies in order to attend the KITB competition. Batang Regency still has people whose awareness of continuing higher education still needs to be higher. Seeing this situation, researchers carried out educational services for students to continue their higher education to face KITB at SMK Ma'arif NU 01 Limpung. This service method uses a participatory educational approach that partners and coordinates with the target school as the object of service. Evaluation of academic activities at Vocational School Ma'arif NU 01 Limpung shows an increase in student interest in continuing higher education. The visible positive attitude changes indicate that this activity was successful in motivating students towards the importance of higher education.